Audio interface for real time navigation - Salviano Soares (2003)
This paper describes a project regarding an orientation system with audio interface providing real time navigation assistance, a most valuable characteristic in situations where the user cannot use a graphical interface. The system is based on a portable platform, such as a portable PC or a PDA, with client/server topology. The server, with high processing capacity, is in charge of finding the best route. It generates the route and messages that will be sent to the client, and has its own real time information updating capabilities. The client checks the users current location, given in real time by a GPS device, and checks if it is inside the route or if it is time to reproduce a message. There are three audio messages types: operational, strategic or tactical. The user may customise the message reproduced, but the operational messages are mandatory. Two files are used under client/server communications. One is created in the client, with the points of origin and destination, essential to calculate the best route. The other is created in the server with directions data, composed by the route and the messages. The communication between the client and the server applications are supported by GPRS, for which a Java-based API was developed.